INVESTMENT COURT SYSTEM SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA PENANAMAN MODAL ASING - Kinanti, Fatma Muthia; Wiko, Garuda (Universitas Brawijaya, 2023)
Investment Court System (ICS) proposed by the European Union (EU) has been ratified through Bilateral Investment Treaty (BIT) between the EU and several partner countries such as Canada, Vietnam and Singapore. A study is needed to get an idea on the ICS mechanism. This is a normative research. The result shows that although there is a mechanism that is not in accordance with the concept of arbitration, the ICS decision is enforced as an arbitration award and is subject to the 1958 New York Convention. Indonesia as one of the countries currently still negotiating with the EU in the formation of an FTA is also still reviewing the adoption of ICS into the text agreement. In addition, although the background and objectives of the ICS are positive, there are still some points of weakness in the provisions of the ICS that will result in obstacles in their implementation which can be seen from the legal, political and technical side.